New psychoactive substances and the risks of consumption in children and adolescents - Viorela Nitescu (Amaltea Medical Publishing House, 2019)
According to the definition established by the European Monitoring Center for Drugs and Drug Addiction (EMCDDA) a "new psychoactive substance is considered any narcotic or psychotropic substance in pure form or in preparations, which is not controlled by the Conventions regarding drugs of the United Nations and which represent a threat to human health comparable to that realized by the substances registered in these conventions considered illicit substances (1). There have been described 4 main classes of new psychoactive substances: synthetic cannabinoids (contained in plant mixtures) , synthetic cathinones (contained in various bath salt powders),natural hallucinogens and piperazines (contained in tablets or capsules). Synthetic cannabinoids are synthetic agonists of cannabinoid receptors, constituting a group of synthetic substances that mimic the effects of Δ 9 tetrahydrocannabinol (THC), the main product from cannabis, responsible for its psychoactive effects (4). Symptoms of poisoning are similar to those of cannabis poisoning but more severe, the clinical picture most commonly comprising: agitation, nausea, palpitations (9). Synthetic cathinones are compounds derived from cathinone - the main constituent of the Catha edulis plant known as KHAT (12). The effects of the consumption are similar to those of amphetamines, methamphetamines or cocaine. Natural hallucinogens are substances that in small doses have the main effect of altering the perception of thinking and mood with the preservation of lucidity along with minor effects on memory and orientation (23,24). Despite the name, these substances rarely produce true hallucinations. The most popular natural hallucinogens are: salvinorin A, psilocybin and psilocyn muscimol and ibotenic acid. Piperazines are synthetic compounds similar to amphetamines but with weaker effects. The best known are: benzylpiperazines and phenylpiperazines (28). Conclusions. The occasional consumption that can lead to acute intoxication or the chronic consumption of new psychoactive substances represents an important health problem occupying a place that should not be neglected in the pathology of adolescents and young people.